Coexpression of calcineurin A and B subunits in various subcellular and synaptic compartments of cerebellar neurons and glia with particular abundance at parallel fiber-Purkinje cell synapses. (July 2022) - Miura, Eriko; Watanabe, Masahiko
Abstract: Calcineurin (CN) is a Ca 2+ /calmodulin-dependent serine/threonine protein phosphatase consisting of catalytic CNA and regulatory CNB subunits, and links activity-dependent Ca 2+ signals to various neural functions. Here we studied CN expression in the mouse brain by producing subunit-specific probes and antibodies. Of five CN subunits. CNAα, CNAβ, and CNB1 mRNAs were predominantly expressed over the brain from early embryonic to adult stage, and all were high in the telencephalon and cerebellum. Protein localization was examined in the cerebellum by immunofluorescence with cellular and terminal markers and by preembedding silver-enhanced immunogold microscopy. CNB1 and CNAβ were co-distributed in subcellular and synaptic elements of various cerebellar neurons and glia, whereas CNAα was exclusive in granule cell elements, including parallel fiber terminals. The present study thus discloses that CNB1 subunit well coexists with one or two CNA subunits in various cerebellar compartments. Moreover, high CN contents are provided to parallel fiber-Purkinje cell synapses, i.e ., CNAα, CNAβ, and CNB1 in their presynaptic side and CNAβ and CNB1 in their postsynaptic side. These findings will be the anatomical basis, at least partly, for the known regulatory roles of postsynaptic CNs in long-term depression and presynaptic CNs in transmitter release function. Highlights: CNB1 is coexpressed with CNAα or CNAβ in brains from early embryonic to adult stage. In the cerebellum, CNB1 and CNAβ well co-exist in various subcellular compartments. CNAα is exclusive in granule cell elements, including parallel fiber terminals. Thus, calcineurin is particularly enriched at parallel fiber-Purkinje cell synapse.